The meat market of tomorrow: clean meat processing facility and meat market in Newtown, Johannesburg - Oosthuizen, Keagan (My University, 2021)
The desire for beef continues to rise globally and the current methods of processing cannot continue to sustainably scale up to meet our demands. Cellular agriculture presents itself as the potential solution in responding to the climate crisis of today created by beef agriculture. Furthermore, this technology promises real meat alternatives without the need for slaughter. The need to alter our methods of processing is also due to beef being an integral part of our everyday life and that it finds itself at the intersection of cultures within South Africa. Moreover, the means of processing beef furthers this idea of intersection as there are various protocols set by cultures stipulating various methods of slaughter and consumption of beef products. The market space where beef and other meat products are sold can also be seen conceptually as a space where cultures intersect and communicate with each other. The abattoir that was once part of the urban fabric has been removed due to the public health concerns, this in turn has created a disconnect between the human, the animal and the processing. This disconnect and disassociation renders the abattoir as a death machine, housed in an anonymous box that generates industrialised products from something that was once organic. The resulting intervention locates itself in Newtown Johannesburg, the site is at the intersection of culture, a prominent butchery network and market history. The architecture aims to reintegrate meat processing into the urban fabric of Johannesburg by means of a pilot clean meat processing facility and meat market. The intervention seeks to challenge the current regulations which oppose the idea of slaughter alongside public programme, through substituting the program of conventional abattoirs with socio-cultural programme. The building continues the concept of new technology through into the structure and materiality with focus on efficiency and sustainability of construction, where the use of conventional materials such as concrete are minimized and substituted with better performing alternatives
A design project submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) July 2021